2021
DOI: 10.29333/ejgm/9764
|View full text |Cite
|
Sign up to set email alerts
|

Fear Perception of the COVID-19 Pandemic in Peru

Abstract: Fear is a natural response to something unknown. In the current scenario, it is important to assess it in relation to the coronavirus disease-19 (COVID-19) pandemic in Latin American countries. Objective: To determine the fear perception according to factors associated with the COVID-19 pandemic in Peru. Methods: An analytical cross-sectional study was conducted based on a virtual questionnaire. The main question was "how much fear people had of COVID-19?", using a scale from zero (without fear) to 10 (very fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 20 publications
3
12
0
3
Order By: Relevance
“…Women experience more health anxiety than males as a result of a public health issue and they experience more fear, and this can be observed due to gender differences [ 21 , 22 ]. Furthermore, women were the most affected in a study conducted in Peru among 3887 persons on the fear perception of the COVID-19 vaccination [ 2 ], as it was in Iraq [ 23 ], which is consistent with the ongoing study. Another notable finding in this study is that young people and mature adults were more fearful of the COVID-19 vaccines, which is consistent with other studies conducted during the COVID-19 pandemic in the Kurdistan area [ 24 ], Iraq [ 23 ], Austria [ 25 ], and the UK [ 26 ].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Women experience more health anxiety than males as a result of a public health issue and they experience more fear, and this can be observed due to gender differences [ 21 , 22 ]. Furthermore, women were the most affected in a study conducted in Peru among 3887 persons on the fear perception of the COVID-19 vaccination [ 2 ], as it was in Iraq [ 23 ], which is consistent with the ongoing study. Another notable finding in this study is that young people and mature adults were more fearful of the COVID-19 vaccines, which is consistent with other studies conducted during the COVID-19 pandemic in the Kurdistan area [ 24 ], Iraq [ 23 ], Austria [ 25 ], and the UK [ 26 ].…”
Section: Discussionsupporting
confidence: 78%
“…Hence, based on an available review, 10-point Likert-type scales were chosen to assess the level of fear of vaccination. They had been successfully used in multiple cross-sectional studies analyzing vaccine fear, vaccine acceptance, and perceived risk of vaccination [ 2 , 11 14 ]. On this scale, individuals are asked to provide a score between 0 and 10 for their level of fear of being vaccinated against SARS-Cov2, ranging from “0-no fear” to “10-very high level of fear.” After completion of data collection, the studied population was divided into three scores of fear which range from 0 to 3 “least fear”, 4 to 6 “medium fear”, and 7 to 10 “highest fear” (2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Peru is one of the countries with the highest mortality rate from COVID-19 per million inhabitants in the world (Taylor, 2021) and has had a significant economic and social impact (Varona and Gonzales, 2021). In this context, high levels of worry, anxiety, and fear of COVID-19 have been described in people living in Peru (Caycho-Rodríguez et al, 2021c;Mejia et al, 2020;Porter et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…When contrasting the levels of severity in the category of anxiety due to COVID-19, and based on gender and age, the study found that there is an association between gender and anxiety due to COVID-19 [X 2 (3, N = 1440) = 30.48; p = .001; V = .15], and that women are the ones who present moderate, severe and very severe anxiety levels (59,1%) [7]. International researches demonstrate that the fear to become infected of COVID-19 is higher in women, people between the ages of 20-29 years-old, 30-39 years-old, 50-59 years-old and older than 60 years-old, as well as those people who had of become infected of COVID-19 [14].…”
Section: Introductionmentioning
confidence: 99%